Platelet-to-Lymphocyte Ratio (PLR) Profile and Neutrophil-to-Lymphocyte Ratio (NLR) in Lung Cancer Patients in Ulin General Hospital Banjarmasin 2017-2018 - Haryati Haryati; Holly Diany (Fakultas Kedokteran Universitas Lambung Mangkurat, 2020)
Abstract: Lung cancer is the leading cause of malignancy in the world reaching up to 13% of all cancer diagnoses. Platelet-to-Lymphocyte Ratio (PLR) and Neutrophil-to-Lymphocyte Ratio (NLR), are promising markers of inflammatory prognosis, clinical decisions for proper management of lung cancer patients. The research used a retrospective analytic observational study as its research method. Samples were taken from Pathology Anatomy Laboratory, and the medical record data of lung cancer patients in Ulin General Hospital Banjarmasin from 2017 to 2018. Male lung cancer patients have percentage of 72% with PLR NLR values by sex are not much different p>0.05. 23% of patients were aged ≥ 65 years and 77% were aged £ 65 years with value p>0.05. Adenocarcinoma reaches 65% with p>0.05. Most metastases are 44% pleural effusion with value p>0.05. Percentage of advanced stage is 90% with a higher PLR NLR value at the end stage. There is a meaningful relationship of NLR with lung cancer stage p<0.05, but no relantionship with PLR p>0.05. PRL and NRL are increased at advanced stage. NRL and PRL did not differ significantly based on age, sex and histology of lung cancer. Keywords: Platelet-to-lymphocyte ratio (PLR), Neutrophil-to-lymphocyte ratio (NLR), lung cancer